ANALISIS KEPUASAN KERJA PEGAWAI DARI PENGARUH FAKTOR KOMPENSASI BUDAYA KERJA DAN PENGEMBANGAN KARIR (STUDI PADA DINAS PENDIDIKAN KABUPATEN BIREUEN) - Rifqi, Muhammad; Kamaruddin, Kamaruddin (IndOmera, 2024)
Job satisfaction increasingly cannot be separated from employee work life which is thought to be influenced by several factors. This research provides an overview of compensation factors, work culture and employee career development. Applying an associative quantitative method, based on a sample survey of 64 employees of the Bireuen Regency Education Office. The analysis uses a path model approach between variables. The research results found (1) Job satisfaction was partially influenced both directly and indirectly by compensation factors, namely 49.09%, work culture factors 61.1% and career development factors 37.54%. (2) Simultaneously compensation, work culture and career development together influence employee job satisfaction by 67%. (3) There is a positive causal relationship between compensation, work culture and employee career development.